A survey on relationships and cultural issues in supply chain management practices in Indian organisations. (17th May 2006) - Singh, Amar; Narain, Rakesh; Yadav, R.C.
Supply Chain Management (SCM) is regarded as a means of improving competitiveness. SCM enables an organisation to respond quickly to customers' demand and to adapt to market variations by forging close relationships with customers and suppliers. Close relationships between buyer and suppliers are essential for the successful implementation of SCM. This paper reports the findings of a survey carried out in Indian manufacturing organisations to ascertain the relationships and cultural issues related to SCM practices. Data have been collected from 54 organisations mainly from automobile, electronics and telecommunication and manufacturing sectors. The findings indicate that Indian organisations are using SCM with the main objective of providing customer satisfaction, by way of offering quality products at low cost, and concentrating on their core competencies, while maintaining long-term relationships with their suppliers. Difficulties encountered in implementing SCM are also discussed.